Effect of feeding graded levels of crude protein on nutrient utilization and feather growth in Lady Amherst's pheasants. Issue 1 (15th December 2015) - Bajpai, Saurabh K.; Das, Asit; Kullu, Singray S.; Saini, Mohini; Sarode, Roshan M.; Sharma, Anil K.
Abstract : In order to find out the optimum level of crude protein (CP) in the diet of captive Lady Amherst's pheasants (LAP) on molt, 18 male birds were randomly distributed into three groups of six each in an experiment based on completely randomized block design. The CP content of the diets of birds in groups I, II, and III was 13.4, 16.5, and 19.1%, respectively. Intake and apparent balance of nitrogen increased linearly ( P  < 0.001) as CP content of the diet increased. Intake and utilization of energy, calcium, and phosphorous were similar among groups. Body mass change and growth rate of feathers were significantly ( P  < 0.01) lower in group I as compared to groups II and III. There was a positive co‐relationship between ME intake and change in body weight ( R 2  = 0.89, F  = 126.4, P  < 0.001). Regression analysis indicates that LAP can maintain body mass when ME supply is 122.2 Kcal/kg BW 0.75 /d. Linear relationships between intake and apparent retention of N, Ca, and P as expressed on mg/kg BW 0.75 /d were all significant. Apparent nitrogen retention, and mean feather growth rate was lower in birds fed diet containing 13.4% CP. Feeding of the diets containing 16.5% CP resulted in improved retention of nitrogen, and mean feather growth rate. Further increase in dietary concentration of CP to 19.1% showed no further improvement. It was concluded that a diet containing 16.5% CP would be optimum for Lady Amherst's pheasants during molt. Zoo Biol. 35:51–60, 2016. © 2015 Wiley Periodicals, Inc.